High mobility group box 1 (HMGB1) mediates nicotine-induced podocyte injury - Datta, Sayantap; Rahman, Mohammad Atiqur; Koka, Saisudha; Boini, Krishna M. (Frontiers in Pharmacology, 2025)
IntroductionCigarette smoking is a well-established risk factor for renal dysfunction. Smoking associated with renal damage bears distinct physiological correlations in conditions such as diabetic nephropathy and obesity-induced glomerulopathy. However, the cellular and molecular basis of such an association remains poorly understood. High mobility group box 1(HMGB1) is a highly conserved non-histone chromatin associated protein that largely contributes to the pathogenesis of chronic inflammatory and autoimmune diseases such as sepsis, atherosclerosis, and chronic kidney diseases. Hence, the present study tested whether HMGB1 contributes to nicotine-induced podocyte injury.Methods and ResultsBiochemical analysis showed that nicotine treatment significantly increased the HMGB1 expression and release compared to vehicle treated podocytes. However, prior treatment with glycyrrhizin (Gly), a HMGB1 binder, abolished the nicotine-induced HMGB1 expression and release in podocytes. Furthermore, immunofluorescent analysis showed that nicotine treatment significantly decreased the expression of podocyte functional proteins- podocin and nephrin as compared to control cells. However, prior treatment with Gly attenuated the nicotine‐induced nephrin and podocin reduction. In addition, nicotine treatment significantly increased desmin expression and cell permeability compared to vehicle treated podocytes. However, prior treatment with Gly attenuated the nicotine-induced desmin expression and cell permeability. Mechanistic elucidation revealed that nicotine treatment augmented the expression of toll like receptor 4 (TLR4) and pre-treatment with Gly abolished nicotine induced TLR4 upregulation. Pharmacological inhibition of TLR4 with Resatorvid, a TLR4 specific inhibitor, also attenuated nicotine induced podocyte damage.ConclusionHMGB1 is one of the important mediators of nicotine‐induced podocyte injury through TLR4 activation.